How Much Should Being Accommodate Becoming? Copyright in Dynamic and Permeable Art - Brauneis, Robert (The Columbia Journal of Law & the Arts, 2020)
Much of the art in genres ranging from participatory art and performance art to environmental art and found art is dynamic, or permeable, or both. That is to say, the art may be unstable or ephemeral, and may invite unpredictable change though the influence of natural or human forces, and it also may have weak, unclear boundaries that blur text and context. Dynamic and permeable art seek to present the world as a continuum in space and time – as becoming –challenging our commitments to boundaries and objects. By contrast, copyright law is firmly committed to being. Its central subject, the work of authorship, must be stable and discrete. Works of authorship can neither change over time, nor have unknown boundaries. One might think that as a consequence, dynamic and permeable art can never be subject to copyright protection. Yet copyright has developed a powerful set of tools to frame various kinds of becoming as being—that is, as stable, bounded objects that can qualify as works of authorship. This essay addresses three of those tools: (1) considering ranges and correlations as copyrightable elements of works; (2) using non-notational, trans-category fixation in audio and video; and (3) considering site-specific and found art as involving compilation. It will consider how each of the tools accommodates dynamic and permeable art, and will then consider the copyright policies that should be taken into account when setting limits for each tool’s use. All three tools raise questions of whether the works they delineate are of sufficient complexity to be more than “ideas,” and whether those works fall into a copyrightable category of work of authorship. Some of the tools also raise distinct issues. For example, when works are composed of ranges and correlations, those ranges and correlations should be conspicuous enough to provide adequate notice, and foreseeable enough that they can be said to have been authored by the artist claiming to have created them. The essay also considers the extent to which the being of copyright does not do full justice to the becoming of dynamic and permeable art, because a work of authorship sufficiently stable and discrete to be the subject of copyright will not include the full, ongoing experience of an open creation and its serendipitous transformations.